2007
DOI: 10.1007/s00520-007-0292-1
|View full text |Cite
|
Sign up to set email alerts
|

Stress and long-term survivors of brain cancer

Abstract: Despite their long-term survival status, long-term survivors of brain cancer continue to experience elevated levels of stress. Predictors of stress in this population are related to familial, emotional, and practical concerns. While the scientific community continues to examine the specific impact of stress on both the physical and mental outcomes of cancer patients, understanding the sources of stress within cancer populations is key in designing targeted interventions to help patients manage the stress assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…In another study, Keir et al . () found that stress did not decrease over time because survivors of >18 months had the same stress levels as those who received a more recent diagnosis. Moreover, distress was found to be negatively associated with social and emotional well‐being, as measured by the FACT‐BR (Kiebert et al .…”
Section: Methodsmentioning
confidence: 97%
“…In another study, Keir et al . () found that stress did not decrease over time because survivors of >18 months had the same stress levels as those who received a more recent diagnosis. Moreover, distress was found to be negatively associated with social and emotional well‐being, as measured by the FACT‐BR (Kiebert et al .…”
Section: Methodsmentioning
confidence: 97%
“…The results of this study suggest that the effect of massage therapy of stress may be additive or cumulative and that once massage therapy is discontinued stress returns but not to original levels. Though no control group was used as a comparison, previous studies by the author indicate that stress and distress continue to be a problem for brain tumor patients throughout the disease continuum [1,3,8]. As such, this study suggests that the massage intervention played a role in reduction of stress for study participants.…”
Section: Discussionmentioning
confidence: 79%
“…A diagnosis of a brain tumor and its subsequent treatment can significantly disrupt a person's life, create stress, and impair QoL [1,2]. Research indicates that patients with brain tumors experience more psychological distress (stress, anxiety, and depression) than other cancer populations [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data also indicate a possible link between acute and sudden psychological stress and the appearance of malignant primitive brain tumours (Cabaniols et al, 2010). Furthermore, long--term survivors of brain cancer continue to experience elevated levels of stress as the fear of recurrence increases with time (Keir et al, 2007). Epidemiological data have described an inverse relationship between Mg content in drinking water and incidence of some types of cancers .…”
Section: Magnesium Interaction With Stress Pathwaysmentioning
confidence: 99%